2014
DOI: 10.7740/kjcs.2014.59.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Anti-inflammatory Activity of Extract from Milling By-products of Sorghum Cultivar, ‘Hwanggeumchal’

Abstract: Sorghum has been consumed as one of the important staple food in the semiarid tropics of Africa and Asia. Sorghum is rich in starch, protein, essential vitamins and minerals and grows relatively well in dry climate regions when it compared with other staple food crops. Sorghum has taken an increased interest due to several studies that report about the beneficial effects of sorghum on human health. In the present study, we investigated the antioxidative and activity of extract of milling by-products (hull and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…When treated with various concentrations of sorghum extract (50, 100, 200, 400, 500 µg/mL), no cytotoxicity was observed in either the hull or grain even at the highest concentration of 500 µg/mL. However, the bran extract maintained a survival rate above 90% at concentrations up to 200 µg/mL [21]. Another study that applied sorghum seed extract at 50, 100, and 200 µg/mL to RAW 264.7 cells found that treatment with 100 µg/mL of extract resulted in cell viability exceeding 89.28 ± 15.30%, indicating robust cell vitality across all tested seed extracts [22].…”
Section: Toxicity Evaluation Of Raw 2647 Cells To Measure Anti-inflam...mentioning
confidence: 97%
“…When treated with various concentrations of sorghum extract (50, 100, 200, 400, 500 µg/mL), no cytotoxicity was observed in either the hull or grain even at the highest concentration of 500 µg/mL. However, the bran extract maintained a survival rate above 90% at concentrations up to 200 µg/mL [21]. Another study that applied sorghum seed extract at 50, 100, and 200 µg/mL to RAW 264.7 cells found that treatment with 100 µg/mL of extract resulted in cell viability exceeding 89.28 ± 15.30%, indicating robust cell vitality across all tested seed extracts [22].…”
Section: Toxicity Evaluation Of Raw 2647 Cells To Measure Anti-inflam...mentioning
confidence: 97%